THEORETICAL AND METHODICAL APPROACHES TO DETERMINATION OF CONCEPT "GREEN BUILDING" - Doroshenko, V.M. (The actual problems of regional economy development, 2018)
The article systematized and explored the main approaches to the interpretation of the definition of "green buildings" in the national and foreign scientific literature. On the basis of system and complex approaches, the author's definition of the concept is proposed, from the standpoint of the concept of sustainable development the prospects of implementation of "green buildings" in Ukraine are analyzed, the economic benefits of "green buildings" are determined, on the basis of the standards of "green building" proposals for key drivers of investment demand formation have been developed. According to the results of the research, the relevance of "green building" in the energy efficiency development of the construction, which has the greatest potential of energy saving, was substantiated.